Collaborative Search Revisited - Morris, Meredith Ringel (Proceedings of CSCW 2013, 2013)
Despite recent innovations in technologies supporting collaborative web search, the features of the primary tools for digital information seeking (web browsers and search engines) continue to reflect a presumption that search is a single-user activity. In this paper, we present the findings of a survey of 167 diverse users’ collaborative web search practices, including the prevalence and frequency of such activities, the information needs motivating collaboration, the methods and tools employed in such tasks, and users’ satisfaction with the status quo. We find an increased prevalence and frequency of collaborative search, particularly by younger users, and an appropriation of “old” technologies like e-mail as well as “new” technologies like smartphones and social networking sites, rather than the use of dedicated collaborative search tools. We reflect on how and why collaborative search practices have changed in the six years since the first survey detailing this phenomenon was conducted, and synthesize our findings to offer suggestions for the design of future collaborative search technologies.